PENGGAMBARAN GANGGUAN STRESS PASCA TRAUMA SEPERTI YANG TERDAPAT DALAM NOVEL IT ENDS WITH US KARYA COLLEN HOOVER - Beiby Luas; Isnawati Lydia Wantasen; Maya Pinkan Warouw (An Nafi': Multidisciplinary Science, 2026)
This study examines the portrayal of Post-Traumatic Stress Disorder (PTSD) in Lily Bloom, the protagonist of Colleen Hoover’s novel It Ends With Us, through the theoretical lens of Gerald Davison’s Abnormal Psychology. A descriptive qualitative methodology was employed, with data collected through close reading and note-taking techniques. The analysis identifies three core PTSD symptom clusters experienced by the character: re-experiencing, avoidance, and hyperarousal. Furthermore, the study reveals trauma-induced impacts on emotional stability, relational dynamics, and life-altering decisions. The research also highlights four recovery mechanisms: writing as therapeutic processing, establishing a support network, assertive decision-making, and self-acceptance. This study underscores literature’s nuanced representation of PTSD and offers insights into psychologically resonant coping strategies within interpersonal trauma contexts. Future research is suggested to explore cinematic representations of PTSD in the film adaptation of It Ends With Us, with particular focus on non-verbal cues such as physical demeanor and facial expressions.